PENGARUH KEBIJAKAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (Fokus Ekonomi, 2009)
This study attempt to respond many question arrounds factors which influenced firm performance in Bursa Eek Indonesia Jakarta. The purpose of this research is to analysis influence of company policies (managerial incentive, capital expenditure and financial leverage) toward firm performance (ROA). Theoritical base used to support this research are two financial theory that had steady namely capital structure and agency theory.This research use sample inside enterprises industry manufactured his shares is active traded in Bursa Efek Indonesia Jakarta. The data used is panel data namely cross section and time series data, period 2004 reaches by 2006. Collecting sample with purposive sampling , where as analytical technique use multiple regression.The result show that capital expenditure variable is not significant influence on firm performance. Managerial incentiveis is positive significant influence on firm performance, but financial leverage is negative significant influence on firm performance.